(untitled) (Comprehensive Journal of Science, 2025)
The research aims to explore the impact of applying digital transformation on developing and improving the academic performance of university professors in light of rapid technological developments. This is done by investing in digital tools and modern educational platforms to enhance the quality of the educational process and increase student interaction. The research adopted the descriptive and analytical approach, and the Accounting Faculty was chosen as the research community, as it is the first nucleus of the establishment of Gharyan University. All the (57) permanent faculty members of the college were targeted during the semester (Fall 2024/2025), who belong to five scientific departments. The questionnaire was also used as the main tool for collecting primary data, which was analyzed using the Statistical Package for the Social Sciences (SPSS). The results of this research: that the Accounting Faculty in Gharyan suffers from lack of information technology to use digital transformation, that the digital infrastructure is insufficient for digital transformation, and the absence of training programs for faculty members related to the use of digital tools. According to these results, a set of recommendations were presented, the most prominent of which are: The Accounting Faculty is the nucleus of the emergence of the University, and has enjoyed a good academic reputation since it was founded. Therefore, the University administration must give it sufficient attention to this Faculty, such as providing the digital infrastructure necessary to adopt digital transformation.